Probiotic yeast BR14 ameliorates DSS-induced colitis by restoring the gut barrier and adjusting the intestinal microbiota. Issue 18 (6th August 2021) - Mu, Zhiyong; Yang, Yijin; Xia, Yongjun; Wang, Fukang; Sun, Yiwei; Yang, Ying; Ai, Lianzhong
Abstract : Saccharomyces cerevisiae BR14 with superior stress tolerance and little toxicity to RAW264.7 cells is obtained. The strain could ameliorate colitis by restoring the gut barrier and microbiota. Abstract : The probiotic Saccharomyces boulardii has been widely used in colitis treatment; however, the beneficial effects of other yeast species are rarely studied. Saccharomyces cerevisiae with great stress tolerance and potential in colitis treatment was investigated in this study. Among 16 yeast strains, BR14, BR54, and BR174 strains showed good stress-resistant capacity, anti-inflammatory activity, and little toxicity to macrophages. As for the colitis mice, BR14 inhibited weight loss the most, as well as the disease activity index and colon shortening. After treatment with BR14, the expression levels of genes related to histological damage were all upregulated. BR14 significantly attenuated the expression levels of TNF-α and IL-6, while the expression of IL-10 was upregulated. Additionally, BR14 rebalanced the intestinal microbial composition of colitis mice by increasing the abundance of Muribaculaceae, Lactobacillus and Rikenellaceae and decreasing the abundance of Turicibacter, Escherichia-Shigell a, Desulfovibrio, and Lachnospiraceae . In summary, BR14 exhibited great potential in alleviating colitis through restoring the gut barrier and adjusting the intestinal microbiota.